2021
DOI: 10.1155/2021/6687386
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Phytochemicals in Experimental Ischemic Stroke: Mechanisms and Potential Clinical Applications

Abstract: Ischemic stroke is a challenging disease with high mortality and disability rates, causing a great economic and social burden worldwide. During ischemic stroke, ionic imbalance and excitotoxicity, oxidative stress, and inflammation are developed in a relatively certain order, which then activate the cell death pathways directly or indirectly via the promotion of organelle dysfunction. Neuroprotection, a therapy that is aimed at inhibiting this damaging cascade, is therefore an important therapeutic strategy fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(49 citation statements)
references
References 431 publications
(789 reference statements)
1
46
0
Order By: Relevance
“…The mechanism of the neuroprotective effects of flavonoids, including kaempferol, is associated with the modulation of autophagy [ 18 ]. Autophagy is a multistep process involving induction, phagophore formation, sequestration, autophagosome formation, and finally fusion of the autophagosome with a lysosome to form an autophagolysosome, which then induces either the death or survival pathway [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of the neuroprotective effects of flavonoids, including kaempferol, is associated with the modulation of autophagy [ 18 ]. Autophagy is a multistep process involving induction, phagophore formation, sequestration, autophagosome formation, and finally fusion of the autophagosome with a lysosome to form an autophagolysosome, which then induces either the death or survival pathway [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Phosphorylated CREB, an activated state of CREB, could up-regulate the expression of BDNF, while BDNF also promotes the activation of CREB through tropomyosin receptor kinase (Trk) B receptors (Zhang et al, 2012;Lan et al, 2014). According to an existing study, the repeated administration of Genistein (a monoterpene isoflavone) was found to improve CREB activity, up-regulate the BDNF expression, and protect the injured nerve of ischemic injury (Xu et al, 2021). Rapid release of BDNF contributed to reverse I/R-induced ischemic injury behaviors in rats .…”
Section: Discussionmentioning
confidence: 99%
“…Despite the numerous and continuous achievements over the years in exploring the mechanisms of EGCG underlying neuroprotection, it has not yet been elucidated so far whether the neuroprotective mechanism of EGCG is associated with the modulations of essential elements and hazardous metal during cerebral ischemic injury. A recent study reveals that cerebral ischemia-induced brain cell death is implicated with three dominant mechanisms and suggests that ionic perturbation is the first, followed by oxidative stress, and inflammation is the last one [ 21 ]. In fact, the occurrence of ionic perturbation is developed within a few minutes after ischemic insult [ 21 ].…”
Section: Discussionmentioning
confidence: 99%